2012
DOI: 10.1088/0004-6256/144/1/19
|View full text |Cite
|
Sign up to set email alerts
|

HAT-P-34b-HAT-P-37b: FOUR TRANSITING PLANETS MORE MASSIVE THAN JUPITER ORBITING MODERATELY BRIGHT STARS

Abstract: We report the discovery of four transiting extrasolar planets (HAT-P-34b-HAT-P-37b) with masses ranging from 1.05 to 3.33 M J and periods from 1.33 to 5.45 days. These planets orbit relatively bright F and G dwarf stars (from V = 10.16 to V = 13.2). Of particular interest is HAT-P-34b which is moderately massive (3.33 M J ), has a high eccentricity of e = 0.441 ± 0.032 at a period of P = 5.452654 ± 0.000016 days, and shows hints of an outer component. The other three planets have properties that are typical of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…HAT-P-37b was identified by the HATNet survey and was confirmed by high-resolution spectroscopy and further photometric observations (Bakos et al 2012). HAT-P-37b is a hot Jupiter with a planetary mass of 1.169±0.103 MJup, a radius of 1.178±0.077 RJup, and a period of 2.797436±0.000007 d. Additional follow-up observations by Maciejewski et al (2016) confirmed these planetary parameters.…”
Section: Hat-p-37bmentioning
confidence: 61%
“…HAT-P-37b was identified by the HATNet survey and was confirmed by high-resolution spectroscopy and further photometric observations (Bakos et al 2012). HAT-P-37b is a hot Jupiter with a planetary mass of 1.169±0.103 MJup, a radius of 1.178±0.077 RJup, and a period of 2.797436±0.000007 d. Additional follow-up observations by Maciejewski et al (2016) confirmed these planetary parameters.…”
Section: Hat-p-37bmentioning
confidence: 61%
“…We observed HAT-P-36b during 4 transit events: On 15 Feb 2018 by using I filter, on 08 Apr 2018 and 06 May 2018 by using V filter in JCBT and on 20 Jun 2018 by using V filter in HCT. The host star is a G5V star with mass, radius and T ef f of 1.03 ± 0.03 M , 1.041 ± 0.013 R and 5620 ± 40 K respectively (Bakos et al 2012). This star is also very similar to the Sun in terms of mass, radius and T ef f .…”
Section: Hat-p-36bmentioning
confidence: 99%
“…We have used the Markov Chain Monte Carlo (MCMC) technique employing Metropolis-Hastings algorithm (Collier Cameron et al 2010) to fit the models with the observed light curves and thus determined the various physical parameters from the best fit. An essential parameter of the model is the orbital period which we have kept fixed at the values given in previously published results (Collier Cameron et al 2010;Gillon et al 2011;Bakos et al 2012;Penev et al 2016;Collins et al 2017). For all the transit events we have assumed circular orbits of the planets.…”
Section: Data Reduction Analysis and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CoRoT-10b (Bonomo et al 2010) and HD17156 (Fischer et al 2007) with a masses of MP= 2.76 MJ and MP= 3.3MJ, respectively, present circularization timescales greater than 20 Gyr. Two eccentric systems of this sample that present short circularization timescales are HAT-P-2b (MP= 8.87MJ, τcirc = 0.7 Gyr, Bakos et al 2007), and HAT-P-34b (MP = 3.33 MJ, τcirc = 0.3 Gyr, Bakos et al 2012). Both systems, however, are significantly younger (∼ 2 Gyr) than EPIC 201498078 (8.5 Gyr), which could help in explaining their non-circular orbits.…”
Section: Orbital Evolutionmentioning
confidence: 99%